The relationship between beginning teachers' engagement with induction program components and student achievement - Holt, Janice Hooper (2011)
The purpose of this study was to examine induction programs in North Carolina during the 2010-2011 school year to determine beginning teachers received the support as recommended by State Board of Education policy. Participants were second-year high school teachers participating in district level beginning teacher induction programs and were teaching courses that required state-mandated standardized tests. Research questions were developed to gather data relative to the components of induction: orientation, mentor support, administrator support, and professional development. Data gathered from the researcher-designed Beginning Teacher Induction Program Survey (BTIPS) were used to answer research questions. A correlational research design was used. Predictor variables were engagement level scores and perceived impact on teaching. The criterion variable was change in student achievement as measured by performance on state standardized tests. Using the Rasch Rating Scale Model, engagement scores were calculated. Pearson r (p < .05) found no significant correlations between engagement with induction components and student achievement. A multiple regression analysis further shows that engagement scores did not significantly contribute to predicting student achievement. The relationship between perceived impact on teaching and student achievement was also examined. Several important findings emerged. The data revealed that teachers in this study had access to and participated in the four induction program components recommended by the State School Board. However for many beginning teachers, support was lacking. Results showed that responding teachers were significantly low engaged in the support provided by administrators as opposed to orientation, mentor support and professional development and were high engaged with the support provided by mentors. Schools and school systems are facing challenging times. The current climate of high stakes testing and uncertain economic conditions magnify the importance of having data to inform educators as they make decisions about their teaching force. Important questions about induction must be answered to best guide future policy. More research is needed that will distinguish the relationship between specific program components and student achievement.